Secondary structures involving the poly(A) tail and other - Moqtaderi, Zarmik (Shared Science Publishers OG, 2014)
In Saccharomyces cerevisiae, previous measurements of mRNA stabilities have been determined on a per-gene basis. We and others have recently shown that yeast genes give rise to a highly heterogeneous population of mRNAs due to extensive alternative 3’ end formation. Typical genes can have fifty or more distinct mRNA isoforms with 3’ endpoints differing by as little as one and as many as hundreds of nucleotides. In our recent paper [Geisberg et al. Cell (2014) 156: 812-824] we measured half-lives of individual mRNA isoforms in Saccharomyces cerevisiae by using the anchor away method for the rapid removal of Rpb1, the largest subunit of RNA Polymerase II, from the nucleus, followed by direct RNA sequencing of the cellular mRNA population over time. Combining these two methods allowed us to determine half-lives for more than 20,000 individual mRNA isoforms originating from nearly 5000 yeast genes. We discovered that different 3’ mRNA isoforms arising from the same gene can have widely different stabilities, and that such half-life variability across mRNA isoforms from a single gene is highly prevalent in yeast cells. Determining half-lives for many different mRNA isoforms from the same genes allowed us to identify hundreds of RNA sequence elements involved in the stabilization and destabilization of individual isoforms. In many cases, the poly(A) tail is likely to participate in the formation of stability-enhancing secondary structures at mRNA 3’ ends. Our results point to an important role for mRNA structure at 3’ termini in governing transcript stability, likely by reducing the interaction of the mRNA with the degradation apparatus.